Preventing self-fertilization: Insights from Ziziphus species - Tel-Zur, Noemi (Frontiers in Plant Science, 2023)
The fitness of self-progeny individuals is inferior to that of their outcrossed counterparts, resulting in a reduction in a plant population's ability to survive and reproduce. To prevent self-fertilization, angiosperms with hermaphrodite flowers may exploit a variety of mechanisms, including synchronous dichogamy and self-incompatibility. Synchronous dichogamy involves two flowering morphs, with strict within-morph synchronization, thereby preventing not only autogamy and geitonogamy but also intra-morph mating. Self-fertilization is also prevented by self-incompatibility, a genetic mechanism that allows the identification and rejection of "self" pollen, thereby preventing both autogamy and geitonogamy. Here, I seek to provide a perspective of flowering in Ziziphus species exhibiting both synchronous (i.e., "Early" morph flowers open in the morning and "Late" morph flowers open in the afternoon) protandrous dichogamy (i.e., pollen dispersal before the stigma becomes receptive) and selfincompatibility.2